Intranasal Delivery of Collagen-Loaded Neprilysin Clears Beta-Amyloid Plaques in a Transgenic Alzheimer Mouse Model - Humpel, Christian (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease (AD) is pathologically characterized by extracellular beta-amyloid (Aβ) plaques and intraneuronal tau tangles in the brain. A therapeutic strategy aims to prevent or clear these Aβ plaques and the Aβ-degrading enzyme neprilysin is a potent drug to degrade plaques. The major challenge is to deliver bioactive neprilysin into the brain via the blood-brain barrier. The aim of the present study is to explore if intranasal delivery of neprilysin can eliminate plaques in a transgenic AD mouse model (APP_SweDI). We will test if collagen or platelets are useful vehicles to deliver neprilysin into the brain. Using organotypic brain slices from adult transgenic APP_SweDI mice, we show that neprilysin alone or loaded in collagen hydrogels or in platelets cleared cortical plaques. Intransasal delivery of neprilysin alone increased small Aβ depositions in the middle and caudal cortex in transgenic mice. Platelets loaded with neprilysin cleared plaques in the frontal cortex after intranasal application. Intranasal delivery of collagen-loaded neprilysin was very potent to clear plaques especially in the middle and caudal parts of the cortex. Our data support that the Aβ degrading enzyme neprilysin delivered to the mouse brain can clear Aβ plaques and intranasal delivery (especially with collagen as a vehicle) is a fast and easy application. However, it must be considered that intranasal neprilysin may also activate more plaque production in the transgenic mouse brain as a side effect.